The fate of condensed tannins during litter consumption by soil animals (Soil Biology and Biochemistry, 2009)
Condensed tannins (CT) can strongly affect litter decomposition, but their fate during the decomposition process, in particular as inﬂuenced by detritivore consumption, is not well understood. We tested the hypothesis that litter CT are reduced by the gut passage of two functionally distinct detritivores of Mediterranean forests, the millipede Glomeris marginata, and the land snail Pomatias elegans, as a ﬁxed proportion of initial litter CT, but more so in Pomatias since snails are known to have a more efﬁcient enzymatic capacity. Contrary to our hypothesis, both detritivore species reduced litter CT to near zero in their faecal pellets irrespective of the wide range in initial leaf litter CT concentrations of 9–188 mg g 1 d m among three Mediterranean tree species (Pistacia terebinthus, Quercus ilex, Alnus glutinosa) and different decomposition stages of their litter. The almost complete disappearance of CT even from some litter types highly concentrated in CT, due to either degradation by gut microorganism or complexation of CT into insoluble high molecular weight structures, suggests a high ‘‘de-tanning’’ efﬁciency across functionally distinct detritivore species. The transformation of CT-rich litter into virtually CT-free faecal pellets by detritivores might be highly relevant for the subsequent decomposition process in ecosystems with a high macrofauna abundance and CT-rich plant species such as Mediterranean forests.